2019
DOI: 10.1109/access.2019.2908524
|View full text |Cite
|
Sign up to set email alerts
|

A Power and Spectrum Efficient NOMA Scheme for VLC Network Based on Hierarchical Pre-Distorted LACO-OFDM

Abstract: Recently, a hybrid multiple access (MA) scheme, non-orthogonal MA (NOMA) combined with orthogonal frequency-division MA (OFDMA), has attracted significant attention in the fifth-generation (5G) wireless communication due to its superior spectrum efficiency. However, the advantage of the hybrid MA scheme cannot be fully realized in visible light communication (VLC) networks, since current optical orthogonal frequency-division multiplexing (OFDM) technologies are unable to provide high spectrum efficiency and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…In [57], Li et al improved the transmitter signal processing of the LACO-OFDM signal. Explicitly, in their TX design, the higher layer signals were pre-distorted by subtracting the clipping distortions of the previous layers from the signal before LB clipping.…”
Section: Complexity Reductionmentioning
confidence: 99%
“…In [57], Li et al improved the transmitter signal processing of the LACO-OFDM signal. Explicitly, in their TX design, the higher layer signals were pre-distorted by subtracting the clipping distortions of the previous layers from the signal before LB clipping.…”
Section: Complexity Reductionmentioning
confidence: 99%
“…The association parameter and the bandwidth are kept fixed here. In [19], similar to energy efficiency, power efficiency maximization of a hybrid multiple access scheme for visible light communication systems has been studied which offers a better bandwidth allocation. The fundamental objective here is to fill the odd subcarriers optimally.…”
Section: Related Work and The Significance Of The Application Of mentioning
confidence: 99%
“…This paper aims for finding the optimal user association, transmit power allocation for APs, and the optimal downlink bandwidth allocation done by the AP for the UEs associated with it. The resource allocation will be done for maximizing r i obtained in (19). The resource allocation problem is formulated as…”
Section: E the Resource Allocation Problemmentioning
confidence: 99%
“…J. Shi et al demonstrated a NOMA-VLC using subcarrier pair-wise coding with transmission distance of 40 cm [17]. In the same year, H. Li et al illustrated a NOMA-VLC using pre-distorted layered asymmetrically clipped OFDM with transmission distances of 40 cm and 70 cm for UE 1 and UE 2 respectively [18]. In 2020, Y. Wang et al demonstrated a three users NOMA-VLC with transmission distance of 120 cm [19].…”
Section: Introductionmentioning
confidence: 99%